Performance of animals fed with green leaf in marandu grass pasture - Machado, Luís Armando Zago; Fabrício, Amoacy Carvalho; Gomes, Alberto; Assis, Paulo Giovani Gall De; Lempp, Beatriz; Maraschin, Gerzy Ernesto (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the performance of animals, fed with green leaves at 4, 8, 12 and 16% of live weight per day, in marandu grass pastures. The experimental design was in complete randomized blocks, with two replications. Animal performance evaluations were made from October 2002 to June 2005, with steers F1 Nelore and Charolais, along the rainy seasons, in Dourados County, Mato Grosso do Sul, Brazil. Four tester animals – 15 to 23 months old – grazed each experimental unit, under continuous grazing and put-and-take technique; the animals were, afterwards, slaughtered. Linear effect was obtained for the intended and observed forage allowances. The consistency of green leaf ingestions by the animals (independently of the offers) was evidenced in esophagus-fistulated steers. The average daily gain showed quadratic response in relation to the green leaf offers, with its optimum level at 11.7% live weight. Stoking rate and live weight gain per hectare presented a negative quadratic effect to the increase of blade dry matter offers. The offers of 8 to 12% live weight allow animals to feed on green leaf blades and to have a good quality diet.
Keywords: Brachiaria brizantha; stocking rate; green leaf intake; daily gain; forage offer